2017
DOI: 10.4049/jimmunol.1500648
|View full text |Cite
|
Sign up to set email alerts
|

IL1R9 Is Evolutionarily Related to IL18BP and May Function as an IL-18 Receptor

Abstract: The IL-1 families of ligands and receptors exhibit similarity of coding sequences, protein structures, and chromosomal positions, suggesting that they have arisen via duplication of ancestral genes. Within these families there is selectivity in ligand-receptor interactions as well as promiscuity. IL-18 and its receptor are members of these families. IL-18 is recognized as binding to the protein products of the IL18R1 and IL18RAP genes, and with high affinity to a separate IL-18 binding protein (IL-18BP). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…IL‐18BP is structurally very similar to the third domain (D3) of the IL‐1R5 and IL‐1R2 receptors, but there is no sequence homology and the encoding gene is different, although it seems that IL‐18BP and IL‐1R2 come from a common ancestral gene . Recently, the evolutionary relationship between IL‐18BP and the orphan receptor IL‐1R9 and IL‐1R10 has been also described, leading to the hypothesis that these receptors may actually act as alternative IL‐18 receptors in brain areas where IL‐18 is produced and active but IL‐1R5 is not expressed . Four isoforms of IL‐18BP have been described from alternative splicing of the human gene, which located on chromosome 11q13 (different from the location of the major IL‐1R gene cluster on chromosome 2q12, which includes the genes for IL‐1R2 and IL‐1R5), and called IL‐18BPa, b, c, and d .…”
Section: Regulation In the Il‐1r Familymentioning
confidence: 99%
See 3 more Smart Citations
“…IL‐18BP is structurally very similar to the third domain (D3) of the IL‐1R5 and IL‐1R2 receptors, but there is no sequence homology and the encoding gene is different, although it seems that IL‐18BP and IL‐1R2 come from a common ancestral gene . Recently, the evolutionary relationship between IL‐18BP and the orphan receptor IL‐1R9 and IL‐1R10 has been also described, leading to the hypothesis that these receptors may actually act as alternative IL‐18 receptors in brain areas where IL‐18 is produced and active but IL‐1R5 is not expressed . Four isoforms of IL‐18BP have been described from alternative splicing of the human gene, which located on chromosome 11q13 (different from the location of the major IL‐1R gene cluster on chromosome 2q12, which includes the genes for IL‐1R2 and IL‐1R5), and called IL‐18BPa, b, c, and d .…”
Section: Regulation In the Il‐1r Familymentioning
confidence: 99%
“…Both IL-1R9 and IL-1R10 are evolutionarily related to IL-18BP. 104 Given that IL-18 is produced by brain neurons in areas where the classical IL-18-binding receptor IL-1R5 is not expressed, 282,283 it can be hypothesized that IL-1R9…”
Section: Even In Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…The interleukin-1 (IL-1) family of cytokines and corresponding receptors constitute one of the main signalling components of inflammation 1 , 2 . It is commonly reported that there are 11 members of the IL-1 ligand family 1 3 and 10 members of the IL-1 receptor family 4 , 5 . The concepts of protein and gene families originally arose from evolutionary analysis where individuals are grouped into families based on shared common ancestry 6 8 .…”
Section: Introductionmentioning
confidence: 99%